Fiqh Rulings Related to Punishment for Theft in Islamic Jurisprudence and Iraqi law: A Comparative Study - Faris Ali Mustafa (QALAAI ZANIST JOURNAL, 2021)
This paper tries to study the punishment Stealing in the Shriah Islamic and iraqian law. The research take punishment Stealing in the Shriah Islamic and iraqian law. including ideal punishment Stealing in the Shriah Islamic and iraqian law and Ideal Stealing punishment Stealing in the Shriah Islamic and iraqian law. and sharper Stealing punishment Stealing in the Shriah Islamic and iraqian law that in shadow Shriah Islamic and iraqian law. I my ago, the maqasidy (objectives) of Shariah have recognized the right of preserving of safeguarding the religion (Din), self, mind (aql) and personal sanctify and humor. By recossily, these rights and extended for Stealing. In addition, these rights include the right of maintaining a suitable and secured Shelter for the refugee and his / her dependents, his right to have access for education and the right for fair trial before the Islamic courts. Although this topic has been extensively dealt and certain areas of the topic that have received scanty coverage. It is hapend that this study will contribute to the literature on that important subjects. This topic is also vital due to the fact that refugee problems have becoming more complex, particularly in the past-word war Two era. We will follow the dedective method in dealing and analyzing the components of this paper bassed on the companative approach. The paper will make use of both primary and secondary sources. The paper will conclude by presenting policy- or united recommendations to improve the conditions of refugee from the Shariah perspective.